Knjižne vezave iz predbaročnega časa - Golob, Nataša (Knjižnica, 2018)
The basis for this paper are conclusions, drawn from a survey of numerous bindings until mid-16th century, kept in libraries and archives in Slovenia, as well as those items that are of Slovenian provenance - but are nowadays found abroad - or closely related with them in terms of cultural history. The purpose is to encourage the targeted research of some aspects of bindings from the pre-Baroque period, aiming to eliminate still persisting grey zones. Among the goals are above all the comprehensive terminological vocabulary, based on development of historical binding structures, a catalogue of blind tools, and a systematic survey of limp-bindings. The paper points out the documentary value of older bindings, which also contain original historical notices, names of binders, locations, dates etc. being important sources in the field of book-anthropology. It shortly presents traditional misconceptions of the aesthetics of bindings, resulting from an evaluation based on a small sample size of bindings, or caused by uncritical repetition of impressions, existing in older bibliography.
Keywords: blind tooling; hard-cover bindings; limp-bindings; mehke vezave; Middle Ages; pečatniki; Renaissance; renesansa; Slovenia; Slovenija; srednji vek; trde vezave